Cytoskeleton and regulation of mitochondrial function: the role of beta-tubulin II - Kuznetsov, Andrey V.; Javadov, Sabzali; Guzun, Rita; Grimm, Michael; Saks, Valdur (Frontiers in Physiology, 2013)
The control of mitochondrial function is a cardinal issue in the field of cardiac bioenergetics, and the analysis of mitochondrial regulations is central to basic research and in the diagnosis of many diseases. Interaction between cytoskeletal proteins and mitochondria can actively participate in mitochondrial regulation. Potential candidates for the key roles in this regulation are the cytoskeletal proteins plectin and tubulin. Analysis of cardiac cells has revealed regular arrangement of β-tubulin II, fully co-localized with mitochondria. β-Tubulin IV demonstrated a characteristic staining of branched network, β-tubulin III was matched with Z-lines and β-tubulin I was diffusely spotted and fragmentary polymerized. In contrast, HL-1 cells were characterized by the complete absence of β-tubulin II. Comparative analysis of cardiomyocytes and HL-1 cells revealed a dramatic difference in the mechanisms of mitochondrial regulation. In the heart, colocalization of β-tubulin isotype II with mitochondria suggests that it can participate in the coupling of ATP-ADP translocase (ANT), mitochondrial creatine kinase (MtCK) and VDAC (ANT-MtCK-VDAC). This mitochondrial supercomplex is responsible for the efficient intracellular energy transfer via the phosphocreatine pathway. Existing data suggest that cytoskeletal proteins may control the VDAC, contributing to maintenance of mitochondrial and cellular physiology.